2009
DOI: 10.7322/jhgd.19914
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao surgimento da respiração bucal nos primeiros meses do desenvolvimento infantil

Abstract: Resumo:Objetivo: os problemas relacionados com a respiração bucal são vários e possuem diversas consequências na saúde humana. O estudo de coorte prospectiva se propõe a determinar os fatores de risco associados ao desenvolvimento da respiração bucal nos primeiros períodos do desenvolvimento infantil. Método: o grupo inicial constituiu-se por 86 bebês com idade de zero a três meses selecionados em áreas de abrangência do município de Vitória-ES. Realizaram-se sete visitas domiciliares, coletando-se dados sobre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
4
0
3
Order By: Relevance
“…Knowledge on its development can assist in the understanding of the pathologies found in this anatomical region, considering that, after birth, several factors can interfere in the normal breathing pattern, such as: anatomical predispositions, environmental factors -such as climatic conditions -sleeping position, artificial feeding, and oral habits (15,16) . Until the age of several months, the child is an obligate nasal breather, considering that, in infants, laryngeal descent has not yet occurred and the soft palate necessarily rests on the epiglottic vallecula, precluding the natural patency of the oral airways (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on its development can assist in the understanding of the pathologies found in this anatomical region, considering that, after birth, several factors can interfere in the normal breathing pattern, such as: anatomical predispositions, environmental factors -such as climatic conditions -sleeping position, artificial feeding, and oral habits (15,16) . Until the age of several months, the child is an obligate nasal breather, considering that, in infants, laryngeal descent has not yet occurred and the soft palate necessarily rests on the epiglottic vallecula, precluding the natural patency of the oral airways (17) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors also observed the impact on sleep quality, since children with dental caries wake up more frequently at night and receive higher quantity of bottles (14) . The influence of oral habits on the orofacial myofunctional system was described in literature (15,16) , especially the prolonged habits of suction and the oronasal breathing in children. However, there is a gap in relation to the association between oral habits and preschool children quality of life, using instruments about OHRQOL.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if the tongue remains low in the oral cavity, the jaw lowers, causing the lips to part. Santos-Neto et al (27) point out that the position of parted lips and the tongue on the floor of the mouth at rest are associated with oral breathing.…”
Section: Discussionmentioning
confidence: 99%